Сутність та види соціального потенціалу підприємства - Kolenda, Nataliia V.; Коленда, Наталія Вікторівна (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті проаналізовано підходи до визначення сутності поняття «соціальний потенціал підприємства» та сформульовано авторське трактування. На основі узагальнення напрацювань науковців щодо класифікації потенціалу визначено основні критерії та розроблено новий підхід до типізації соціального потенціалу підприємства. Дано характеристику визначеним типам потенціалу.The analyzes of approaches to defining the essence of the concept of «social potential of the enterprise» in the article. On the basis of which identified the main signs of social potential of the enterprise. Author 's interpretation of the concept as the possibility of individuals and the collective as a whole to achieve the mission, strategic goals of the enterprise and meet their own needs, which are formed and implemented in the in the process of debugging social relations and provide social development of the individual. Defined classification criteria of the social potential of the enterprise, in particular: the level of implementation, the degree of satisfaction of needs, the nature of carriers the potential, quantitative measurement, the level of compliance to the aim pursued, a form of manifestation, the form of existence, the qualitative composition,t the level of permanence. Given the interpretation of each type of social potential of the enterprise.
The Essence and Types of Social Potential of the Enterprise
Keywords: соціальний потенціал підприємства; соціальний зв’язок; соціальний розвиток; соціальний капітал; соціальна мережа; social potential of the enterprise; social communication; social development; social capital; social network